(untitled) (Current Horticulture, 2023)
Tuberose (Polianthes tuberosa Linn.) is major bulb crop growing in both tropical and subtropical areas. The popularity of tuberose is due to as it occupies prime position in cut and loose flower, essential oils extraction and landscaping. The main problem in conventional tuberose breeding is lack of genetic variability, self-incompatibility and seed sterility. To achieve the rapid evaluation, induced mutation was opted. It is one of important pathway to find variability in vegetatively propagated species. So far 3,300 officially released mutants available in 170 different species from 60 countries. Mutation induction in tuberose was carried out by physical mutants like X-rays, Gamma Rays and chemical mutagens like EMS and DES. Till now two induced mutants namely, Rajat Rekha (Silver strip) and Swarna Rekha (Golden Strip) with leaf variation have been developed at CSIR-National Botanical Research Institute, Lucknow (Uttar Pradesh). More mutation works was also carried out through induced mutation. In future still there is wide scope opened for induction of different mutants like colour variation, change in petal shape, altered flower arrangement in spike, long and short spike mutants in tuberose.